Efficacy of Hemiarthroplasty vs. Locking Plate Fixation for Proximal Humerus Fractures: A Meta-Analysis - Deng, Jiali; Zhang, Shuai; Yu, Yuanyuan; Zhang, Li; Zhang, Li; Jiang, Wen; Yang, Kai; Xi, Xiaoyan (Frontiers in Surgery, 2021)
Background: Proximal humerus fractures (PHFs) are common in the clinic and account for approximately 6% of all adult fractures. Hemiarthroplasty (HA) or locking plate fixation (LP) is currently recommended for the treatment of complex PHFs; however, there is no uniform standard for optimal surgical treatment or functional recovery. We conducted a meta-analysis to compare the efficacy of LP and HA in the treatment of PHFs. Methods: Relative studies associated with HA and LP were searched in December 2020 in the PubMed, Embase, Cochrane Library, and OVID databases. The quality of the studies, functional outcomes (including the Constant-Murley score (CMS), American Shoulder and Elbow Surgeons Score (ASES), Simple Shoulder Test (SST), Short Form Health Survey (SF-12v2), complications, and reoperation rate were extracted and analyzed by STATA 14.0 software. Results: A total of 958 patients from 12 studies were included in this meta-analysis. The meta-analysis showed that patients treated with LP had a significantly lower reoperation rate, a higher complication rate and a higher CMS score than those treated with HA. There were no significant differences in ASES, SST, or SF-12v2 scores between treatment groups. Conclusions: Compared to HA, LP exhibited better clinical efficacy in some aspects. However, large sample, randomized, controlled studies are needed for further validation.